2020
DOI: 10.3390/ijms21176319
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Cell Modulation by Tumor-Derived Extracellular Vesicles

Abstract: Extracellular vesicles (EV) can carry proteins, RNA and DNA, thus serving as communication tools between cells. Tumor cells secrete EV, which can be taken up by surrounding cells in the tumor microenvironment as well as by cells in distant organs. Tumor-derived EV (TEV) contain factors induced by tumor-associated hypoxia such as heat shock proteins or a variety of microRNA (miRNA). The interaction of TEV with tumor and host cells can promote cancer angiogenesis, invasion and metastasis. Myeloid cells are widel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 161 publications
(220 reference statements)
0
25
0
Order By: Relevance
“…Consistently, it has been demonstrated that the exosome-mediated transfer of a non-coding RNA (hY4) to monocytes contributes to cancer-related inflammation and immune escape via PD-L1 expression [ 117 ]. Furthermore, it is known that malignant cells support myeloid-derived suppressor cells’ (MDSC) inducing capacities [ 118 ]. Remarkably, under the effect of miR-155-enriched exosomes from CLL patients, monocytes differentiate into MDSC.…”
Section: The Immune Evasion Mechanism Of Blood Cancers: Focus On Ementioning
confidence: 99%
“…Consistently, it has been demonstrated that the exosome-mediated transfer of a non-coding RNA (hY4) to monocytes contributes to cancer-related inflammation and immune escape via PD-L1 expression [ 117 ]. Furthermore, it is known that malignant cells support myeloid-derived suppressor cells’ (MDSC) inducing capacities [ 118 ]. Remarkably, under the effect of miR-155-enriched exosomes from CLL patients, monocytes differentiate into MDSC.…”
Section: The Immune Evasion Mechanism Of Blood Cancers: Focus On Ementioning
confidence: 99%
“…Tumor-associated macrophages have been shown to consistently react to signals received from tumors, including directly responding to tumor-derived EVs which can trigger multiple forms of macrophage activation and polarization (Arkhypov et al, 2020). Macrophages are activated by a myriad of factors that cause them to differentiate from their original monocyte progenitor.…”
Section: Macrophage Polarization In the Tumor Microenvironmentmentioning
confidence: 99%
“…MDSCs possess potent immunosuppressive functions and are involved in cancer, autoimmune, and chronic inflammatory diseases [24]. Tumor-derived EVs may play active roles in both chronic inflammation and conversion of myeloid cells into MDSCs and other immunosuppressive phenotypes [25]. The examples include polarization of myeloid cells into pro-tumorigenic M2 macrophages by glioblastoma-derived EVs [26] and induction of the immune checkpoint molecule PD-L1 on circulating monocytes by EVs from melanoma and chronic lymphatic leukemia [27,28].…”
Section: Introductionmentioning
confidence: 99%